The Provisions of Artificial Wombs: A Fundamental Jurisprudential Study - Al-athamneh, Ghaidaa Hisham; Al-rifai, Rudaina Ibrahim (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to explain the concept of the uterus, its structure, and its physiological functions. It then clarifies the concept of the artificial womb, its origin, and the reasons for its use. Furthermore, it examines the Islamic legal adaptation for using artificial wombs for prematurely born embryos and fertilized eggs in their early stages of growth based on the reasons necessitating their use. Artificial wombs are a new medical issue that requires a clear religious stance. Methods: The study relies on a descriptive method based on induction and tracking of particulars related to the subject through books, research papers, articles in journals, and newspapers. It also involves analyzing religious texts to reach a ruling on emerging issues by referring to jurisprudential efforts and opinions and building upon them. This study addresses contemporary issues that are widely discussed and frequently questioned by medical specialists regarding the feasibility of benefiting from scientific advancements and techniques that aid in pregnancy and childbirth Results: The study concluded that it is obligatory to use artificial wombs for placing prematurely born embryos to save their lives from perishing. The use of artificial wombs for placing fertilized eggs cannot be absolutely permitted nor completely prohibited; the Islamic ruling on its use is based on the reason that necessitated it. It is permissible to use it, but under specific regulations and conditions. Conclusions: The study recommends providing doctors who use artificial wombs with the relevant jurisprudential rulings and ethical principles through conferences and medical jurisprudential workshops related to the topic. Additionally, it suggests enacting laws that impose penalties on anyone who deals with these matters in ways that contradict ethics and religious morals.